2020
DOI: 10.18502/jovr.v15i2.6748
|View full text |Cite
|
Sign up to set email alerts
|

Alport Syndrome and Femtosecond Laser Assisted Cataract Surgery

Abstract: We report the surgical management of a patient with bilateral anterior lenticonus due to Alport syndrome using femtosecond laser-assisted cataract surgery (FLACS) and the Optiwave Refractive Analysis (ORA) system. A 38-year-old man with Alport syndrome presented to our department with visual loss due to anterior lenticonus in both eyes. Adjustments during bilateral FLACS were performed with the software’s calipers to manually delineate the anterior capsulotomy. Multifocal toric intraocular lenses (IOLs) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some authors have described FLACS for anterior lenticonus through separate case reports. [ 68 69 70 71 72 73 ] Using the LenSx ® system, Ecsedy et al [ 69 ] created a 4.8-mm anterior capsulotomy using a pulse energy of 5 µJ with 4 µm spot separation and 3 µm layer separation. On scanning electron microscopy, there was a uniform serrated profile created through the capsule.…”
Section: Anterior Lenticonus and Other Indicationsmentioning
confidence: 99%
“…Some authors have described FLACS for anterior lenticonus through separate case reports. [ 68 69 70 71 72 73 ] Using the LenSx ® system, Ecsedy et al [ 69 ] created a 4.8-mm anterior capsulotomy using a pulse energy of 5 µJ with 4 µm spot separation and 3 µm layer separation. On scanning electron microscopy, there was a uniform serrated profile created through the capsule.…”
Section: Anterior Lenticonus and Other Indicationsmentioning
confidence: 99%
“…Recent studies 42 , 43 , 44 on cataract patients with Fuchs endothelial corneal dystrophy indicated that FLACS may perform better than conventional phacoemulsification in the reduction of corneal endothelial cell loss and CCT changes. This trial of FLACS was expanded to more complex cases such as Marfan syndrome, subluxated lens, 45 , 46 Alport syndrome, 47 and shallow anterior chamber. 48 , 49 …”
Section: Femtosecond Laser-assisted Cataract Surgerymentioning
confidence: 99%